Long-Term Outcomes of Ledipasvir/Sofosbuvir Treatment in Hepatitis C: Viral Suppression, Hepatocellular Carcinoma, and Mortality in Mongolia - Amgalan Byambasuren; Buyankhishig Gyarvuulkhasuren; Byambatsogt Erdenebat; Khurelbaatar Nyamdavaa; Oidov Baatarkhuu (Viruses)
(1) Background: Hepatitis C virus (HCV) infection poses a significant health burden, particularly in Mongolia, where the HCV prevalence is notably high. This study evaluates the long-term outcomes of HCV treatment with ledipasvir/sofosbuvir, focusing on mortality, viral relapse, and hepatocellular carcinoma (HCC) development. (2) Methods: This prospective, longitudinal cohort study initially enrolled patients with chronic HCV in Mongolia between 2016 and 2017, focusing on those who completed the five-year follow-up (n = 303). The study measured long-term mortality, HCC development, and viral relapse, employing non-invasive methods to assess liver fibrosis and liver function. (3) Results: At the outset, 98.2% of the patients achieved undetectable HCV RNA levels. Over five years, 6.27% experienced viral relapse and 3.30% developed hepatocellular carcinoma (HCC), with a mortality rate of 5.94%. In a multivariable analysis, the significant predictors for HCC occurrence included age (OR = 1.081, 95% CI = 1.021–1.145), liver cirrhosis (OR = 5.866, 95% CI = 1.672–22.577), and GGT level (OR = 1.011, 95% CI = 1.004–1.018). The independent predictors of mortality included age (OR = 1.083, 95% CI = 1.024–1.147), liver cirrhosis (OR = 6.529, 95% CI = 1.913–22.281), and GGT (OR = 1.011, 95% CI = 1.004–1.017). (4) Conclusions: This study demonstrates that ledipasvir/sofosbuvir effectively suppresses HCV initially and maintains low viral relapse rates over the long term. However, it emphasizes the need for continued management to reduce the long-term risk of HCC and mortality, especially in patients with severe liver fibrosis or cirrhosis.